Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/ncb2490
|View full text |Cite
|
Sign up to set email alerts
|

Id proteins synchronize stemness and anchorage to the niche of neural stem cells

Abstract: Stem-cell functions require activation of stem-cell-intrinsic transcriptional programs and extracellular interaction with a niche microenvironment. How the transcriptional machinery controls residency of stem cells in the niche is unknown. Here we show that Id proteins coordinate stem-cell activities with anchorage of neural stem cells (NSCs) to the niche. Conditional inactivation of three Id genes in NSCs triggered detachment of embryonic and postnatal NSCs from the ventricular and vascular niche, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 46 publications
5
117
0
1
Order By: Relevance
“…Loss of Id in iGICs induced the bHLH-ID targets Rap1gap and Cdkn1c (13,35) and led to morphological and molecular changes indicative of multilineage neural differentiation (Supplemental Figure 7, A-C). These effects occurred in the absence of signs of apoptosis (Supplemental Figure 7D).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Loss of Id in iGICs induced the bHLH-ID targets Rap1gap and Cdkn1c (13,35) and led to morphological and molecular changes indicative of multilineage neural differentiation (Supplemental Figure 7, A-C). These effects occurred in the absence of signs of apoptosis (Supplemental Figure 7D).…”
Section: Figurementioning
confidence: 99%
“…Id-cTKO) mice (13). HrasV12-Cre-ER-shp53 lentiviral particles were injected in the hippocampi of 4-week-old Id-cTKO mice, and tumor initiation/progression was examined.…”
Section: Suppression Of Id Function Impacts Tumor Maintenance Of Hggmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study (Fraidenraich et al 2004) found that deleting three out of the four Id genes (Id1,2,3 triple gene knockout) caused complex cardiac defects but did not ablate the heart in these embryos, thereby indicating that earlier cardiac specification could still occur. Given the functional similarity of Id family members (Lyden et al 1999;Fraidenraich et al 2004;Kee and Bronner-Fraser 2005;Niola et al 2012Niola et al , 2013, we reasoned that either redundant or compensatory activity of Id4 might allow heart formation to occur in triple-knockout embryos. To test this hypothesis, we genetically ablated all four Id gene members using a CRISPR/Cas9 genome-editing strategy in mouse embryos.…”
Section: Id Proteins Promote Cardiogenic Mesoderm Formation In Vivomentioning
confidence: 99%